The Implementation of the Arabic Speech Program in Teaching Arabic Speaking Skills at Bustanul Ulum Arabic Language Center - Syaqifah, Iklil; Zaini, Muhammad Ardy (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2023)
At Bustanul Ulum boarding school, Arabic language enthusiasts expressed concerns about the instruction of Arabic speech skills. To address this, they dedicated their vacation time to practicing through the Arabic Public Speaking Program at the Arabic Language Center. This study utilizes qualitative research to describe the implementation of the program. Data were collected through interviews, observation, and document analysis. The researcher employed Millis' and Haberman's theory for data analysis, involving collection, reduction, presentation, deduction, and confirmation. Findings reveal that 1) the program employs the Drill method, encompassing basic and real training, with strategies such as memorization and structural clarification. 2) Driving factors include student interest, self-confidence, linguistic fluency, knowledge of Arabic grammar, and memorization skills. Hindering factors involve time constraints and students' literary and rhetorical limitations. Overall, the Arabic Public Speaking Program proves effective in enhancing speech skills, catering to enthusiastic students despite certain obstacles. المراجع فائزة عزة. 2021. تطبيق طريقة المباشرة في ترقية مهارة الكلام. إجطلجا، المجلة. محمد عز المعالي. 2021م. إدارة أنشطة الخطابة لترقية مهارة الكلام بمعهد النقاية الإسلامي سومنب. مالانج: جامعة مولانا إبراهيم الإسلامية الحكومية مالانج. عزا يوريكا. 2018م. تنفيذ تعليم مهارة الكلام في برنامج الرغبات و الملكات معهد الجامعة الإسلامية الحكومية جمبر للسنة الدراسية 2017/2018م. جمبر: جامعة الإسلامية الحكومية بجمبر. تيان، لادي. 2021م. أثر تعليم الخطابة العربية على ترقية مهارة الكلام لطالبات مدرسة المعلمات بمعهد بيت الأرقام جمبر للسنة الدراسية 2020/2021م. جمبر: جامعة الإسلامية الحكومية بجمبر. رفاع شافي حلوى سلسبيلا، 2019، تعليم الخطابة الممبرية لممارسة مهارة الكلام باللغة العربية في معهد التربية الإسلامية الحديثة الأزهري لسمانا اجيباراع بانيوماس جمبر: جامعة الإسلامية الحكومية بجمبر. Al-hufaz santri, 2021. Surah An-Nahl. Bandung: Cordoba ayat 125. Undang-undang Republik Indonesia Nomor 20 Tahun 2003 tentang system Pendidikan Nasional, pasal 1. fikri, Khairul. 2021. Implementasi Bahasa Arab sebagai bahasa internasional. Indonesia: Guepedia. Amalia, yuniarti. 2018. “faktor-faktor Kesulitan Siswa dalam Membaca Teks Bahasa Arab” dalam jurnal Penelitian Bahasa, sastra, dan budaya Arab volume 1. Muhaimin, suti;ah dan sugeng, 2009. Menejemen Pendidikan. Jakarta: Kencana. Syukir, Asmuni. 2013. Dasar-Dasar Strategi Dakwah Islam. Surabaya: Al Ikhlas Suhandang, Kustandi. 2009. Retorika Strategi Teknik dan Teknik Pidato. Bandung: Nuansa, Cetakan ke-1. Partanto. Al-Barry, Dahlan. 2001. kamus Ilmiah Populer, Arkola. Yogyakarta: deepublish publisher. Ilahi, Wahyu. 2010. Komunikasi Dakwah. Bandung: PT Remaja Rosdakarya. Ath-Thalib, Hisyam. 1996. Panduan Latihan untuk Jurus Dakwah. Jakarta: Media Dakwah. Anwar, A. A. 2007. Evaluasi Kerja Sumber Daya Manusia. Jakarta: PT.Refika Aditama. Suhandang, Kustandi, 2015. Retorika Strategi Teknik dan Teknik Pidato. Bandung: Nuansa, cetakan II